Online Teaching during the Covid-19 Pandemic: The Philippine Experience - Gallespen, Ervie Emelda (JPAIR Institutional Research, 2021)
Teachers shifted to online teaching when schools were shut down due to the Coronavirus-19 global pandemic. The study determined the experiences, challenges, and responses of teachers while doing online teaching. A survey through Microsoft Teams was administered to 194 Senior High School and College teachers in Riverside College, Bacolod City, Philippines. Findings revealed that support system was experienced by the teachers through the webinars provided, the assistance of colleagues and housemates, and the help extended by parents to their children. The challenges identified were the extent of students’ learning as observed and the teachers’ learning climate, their living conditions, work environment, devise used, and connectivity. A positive response was reflected in the teachers’ adaptability, level of enjoyment, and work-life balance. Their readiness in the resumption of face-to-face classes resulted from the stress experienced. Teachers’ stress levels differed when they were compared according to their department and employment status. Their satisfaction towards the Microsoft Teams platform significantly differed when they were grouped according to their department. No significant difference was observed in the teachers’ extent of readiness in the resumption of face-to-face classes when they were compared according to their department, employment status, and the number of subject load preparations. The results consider the impact of online teaching on the students’ learning and the teachers’ well-being.